Analysis of Agents’ Readiness in Taking Calls: Perspectives on Language Assessments and its Effectiveness - Contreras, Clarise Tan (English Education Department at FKIP Nommensen University, 2024)
BPO industry is one of the most popular jobs of choice by many young people in the Philippines. Its popularity is due to the fact that the salary is competitive and it does not discriminate by giving equal chances to jobseekers regardless of their age, gender, or educational attainment. As there are numerous BPO companies in the Philippines, some find it as an opportunity to enhance their communication skills before applying for the job of their dreams. With that, this paper aims to identify the different language assessment tools and tests provided during training and measure how effective it is to prepare the agents in taking live calls. This study also presents common opportunities agents less than 90-day tenure experience and the interventions done by their supervisors to meet the operation needs.